2017
DOI: 10.1016/j.bbamcr.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases outside vertebrates

Abstract: The matrix metalloproteinase (MMP) family belongs to the metzincin clan of zinc-dependent metallopeptidases. Due to their enormous implications in physiology and disease, MMPs have mainly been studied in vertebrates. They are engaged in extracellular protein processing and degradation, and present extensive paralogy, with 23 forms in humans. One characteristic of MMPs is a ~165-residue catalytic domain (CD), which has been structurally studied for 14 MMPs from human, mouse, rat, pig and the oral-microbiome bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 144 publications
0
24
0
Order By: Relevance
“…Zymogenicity in MPs was first structurally analysed in the 1990s for the funnelin metallocarboxypeptidases (Coll et al, 1991;Gomis-Rü th et al, 1995;Gomis-Rü th, 2008) and for mammalian MMPs (Becker et al, 1995;Morgunova et al, 1999;Tallant, Marrero et al, 2010). MMPs are found, often in several copies, in animals, plants, fungi, archaea, bacteria and viruses (Marino-Puertas et al, 2017), with 23 paralogs in humans. Mammalian MMP zymogens are inhibited by 70-90residue PSs upstream of the CD through a cysteine within a conserved motif, PRCGXPD.…”
Section: Promirolysin Latency In the Context Of Other Mpsmentioning
confidence: 99%
“…Zymogenicity in MPs was first structurally analysed in the 1990s for the funnelin metallocarboxypeptidases (Coll et al, 1991;Gomis-Rü th et al, 1995;Gomis-Rü th, 2008) and for mammalian MMPs (Becker et al, 1995;Morgunova et al, 1999;Tallant, Marrero et al, 2010). MMPs are found, often in several copies, in animals, plants, fungi, archaea, bacteria and viruses (Marino-Puertas et al, 2017), with 23 paralogs in humans. Mammalian MMP zymogens are inhibited by 70-90residue PSs upstream of the CD through a cysteine within a conserved motif, PRCGXPD.…”
Section: Promirolysin Latency In the Context Of Other Mpsmentioning
confidence: 99%
“…Although the cysteine-switch mechanism was derived from mammalian MMPs, sequence analyses revealed that plant MMPs likely also contain a pro-segment with a cysteine-switch motif, which, however, may occasionally diverge from the consensus 98,99 . Accordingly, this mechanism of latency seems to be widely conserved across eukaryotic MMPs 99 .…”
Section: Scheme 4 -Structures Of Prototypic Mp Zymogens (Ii) (A) Entmentioning
confidence: 99%
“…Although the cysteine-switch mechanism was derived from mammalian MMPs, sequence analyses revealed that plant MMPs likely also contain a pro-segment with a cysteine-switch motif, which, however, may occasionally diverge from the consensus 98,99 . Accordingly, this mechanism of latency seems to be widely conserved across eukaryotic MMPs 99 . Furthermore, the more distantly related members of the gametolysin family of MPs from green algae, such as unicellular Chlamydomonas reinhardtii and multicellular Volvox carteri, may likewise operate through a cysteine switch [99][100][101][102] .…”
Section: Scheme 4 -Structures Of Prototypic Mp Zymogens (Ii) (A) Entmentioning
confidence: 99%
“…However, orthologs of MMPs have been reported to occur rarely in fungi, strictly phylum Ascomycota and no activity data are available (Cerdà-Costa and Gomis-Rüth, 2014;Marino-Puertas et al, 2017). M-peptidases have also been implicated as virulence factors in various organisms (Gravi et al, 2012).…”
Section: Metallopeptidases and Cysteine Proteases Are The Most Abundamentioning
confidence: 99%